pCO2 values in asphyxiated infants under therapeutic hypothermia after tailored respiratory management: a retrospective cohort study - Serrao, Francesca; Tiberi, Eloisa; Verdolotti, Tommaso; Romeo, Domenico Marco Maurizio; Corsello, Mirta; Pede, Elisa; Cota, Francesco; Costa, Simonetta; Gallini, Francesca; Colosimo, Cesare; Mercuri, Eugenio Maria; Vento, Giovanni (Frontiers in Pediatrics, 2024)
Background Hypoxic-ischemic encephalopathy (HIE) represents one of the major causes of neonatal death and long-term neurological disability. Both hypoxic-ischemic insults and therapeutic hypothermia (TH) can affect respiratory function. Currently, there is no evidence regarding optimal respiratory management in these infants. Methods This is a retrospective cohort study examining newborns with HIE treated with TH between January 2015 and September 2020. The study population was divided into two groups based on different respiratory assistance during TH: spontaneous breathing (Group A) or mechanical ventilation (Group B). The primary outcome of the study was the mean pCO2 ± SD evaluation during TH in ventilated and non-ventilated asphyxiated infants. The secondary outcome was the correlation between ventilation strategy and short-term neurologic outcome according to Rutherford et al.'s MRI scoring system. Results A total of 126 newborns were enrolled, 75 in Group A and 51 in Group B. Respiratory management was individualized, and volume guarantee (VG) ventilation was the first choice for ventilated infants. Group B infants showed more severe conditions at birth. During TH, ventilated infants showed optimal mean pCO2 comparable with those breathing spontaneously (40.6 mmHg vs. 42.3 mmHg, respectively, p 0.091), with no significant difference in pCO2 standard deviation between (7.7 mmHg vs. 8.1 mmHg, respectively, p 0.522). Mean pH, pH standard deviation, mean pO2, pO2 standard deviation, and mean respiratory rate also did not differ between groups. MRI patterns of brain injury predictive of abnormal neurodevelopmental outcomes were similar in both groups. Logistic regression analysis demonstrated that only umbilical cord arterial blood pH-affected MRI lesions were associated with poor neurodevelopmental outcomes (OR 1.505; CI 95% 1.069–2.117). Conclusions Infants cooled after HIE should receive individualized respiratory management, not necessarily involving intubation. In those infants requiring mechanical ventilation, a volume-targeted strategy appeared to be effective in maintaining stable blood gas levels. Short-term neurological outcomes appeared comparable in ventilated and non-ventilated infants.